ASYMMETRY OF SELF-SUFFICIENCY IN POTATO PRODUCTION IN THE EUROPEAN UNION - Krzysztof Firlej; Sebastian Kubala (Annals of the Polish Association of Agricultural and Agribusiness Economists, 2018)
Potato cultivation has been recognized for many years as the basic source of food for the population onall continents. The purpose of the article was to attempt to assess the self-sufficiency of potato productionin EU countries as a product of great importance on agricultural markets. The study focused on technicaland economic self-sufficiency. As the individual indicators have shown, the countries of the EuropeanUnion are characterized by a significant differentiation in terms of self-sufficiency.